2022
DOI: 10.1002/jlb.3a0322-151r
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate reduces neutrophil extracellular trap formation and tissue injury in severe acute pancreatitis

Abstract: Neutrophil extracellular traps (NETs) promote intra‐acinar trypsin activation and tissue damage. Therefore, reducing NET formation can reduce tissue damage in severe acute pancreatitis (SAP). However, NET formation pathways may differ among disease models. In this study, we evaluated the role of the myeloperoxidase–neutrophil elastase (NE) pathway in NET formation in SAP. SAP was induced by intraperitoneal injection of cerulein and LPSs in mice, and NE activity was inhibited by GW311616. Pancreatic tissues wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 86 publications
(186 reference statements)
0
1
0
Order By: Relevance
“…Clarifying the endogenous mechanisms underlying AP progression could help to clinically treatment and improve prognosis. Besides the classical role of neutrophils, numerous findings suggest that neutrophil-derived NETs play an important role in the pathophysiology of AP (8,(25)(26)(27). Based on the role of Pselectin in neutrophil functions, our study focused on the relationship between the highly expressed P-selectin and NETs in AP and found that in human neutrophils P-selectin is an important stimulus of NETs formation, which is consistent with the findings of Etulain et al in mouse neutrophils (20).…”
Section: Discussionmentioning
confidence: 99%
“…Clarifying the endogenous mechanisms underlying AP progression could help to clinically treatment and improve prognosis. Besides the classical role of neutrophils, numerous findings suggest that neutrophil-derived NETs play an important role in the pathophysiology of AP (8,(25)(26)(27). Based on the role of Pselectin in neutrophil functions, our study focused on the relationship between the highly expressed P-selectin and NETs in AP and found that in human neutrophils P-selectin is an important stimulus of NETs formation, which is consistent with the findings of Etulain et al in mouse neutrophils (20).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cyclosporine A uses the calcineurin pathway to reduce NETs [85], while the antioxidants N-acetylcysteine, ethotrexate, trolox, tempol [86], epigallocatechin-3-gallate [87], and diphenyleneiodonium chloride (DPI) [88] decrease NETs by reducing mitochondrial ROS formation [85]. DPI also reduces NET formation through the PKC-βII pathway [89] like metformin.…”
Section: Pharmacological Modulation Of Netsmentioning
confidence: 99%
“…Other compounds including those derived from green tea [188] and ginger [189] have been demonstrated to reduce ROS production and NET expression.…”
Section: Other Therapiesmentioning
confidence: 99%